Musical Studies on “Timang Tuah” Ritual by the Ibans in Sarawak - Laura Pranti, Tutom; Siti Marina, Kamil (ICONARTIES, 2019)
This paper seeks to explore the musical journey of a symbolic ritual among the Ibans in Sarawak Borneo Malaysia known as Timang Tuah as an effort to preserve and spread awareness to the global community of its existence. Adapting the qualitative approach in collecting and processing the data, this paper aims to describe the processes involved in the ritual and investigate the relevance of the ritual among the current Iban community in Sarawak. Semi structured interviews and passive observations were carried out to record the whole process of the ritual and additionally questionnaires were distributed to investigate its resonance among the audience. Findings have shown that the ritual is done according to specific purposes which includes appeasing spirits during harvest and ushering in luck. The melody of how the songs are carried out also depends on the range and the skills inherited by the lemambang. It was also revealed that the younger generation are not aware of this ritual thus signaling the needs of preservation efforts by the authority involved.